Regional Aspects of the Development of Clustering in the Dairy Branch - Ivan Novikov (Comparative Economic Research. Central and Eastern Europe, 2019)
In this paper, we study the classical and modern approaches to the formation of regional agro-industrial clusters. In the current market conditions, the creation of a cluster based on the existing regional infrastructure is impractical. In most cases, clusters are called holding structures that include the full cycle of production, processing and marketing of agricultural products, for example, "dairy clusters" - there are traditional groups of companies that formally follow the classical cluster principles, but do not give individual participants in the production process sufficient organizational and legal autonomy. The conditions for the development of innovation within the cluster, as well as the mechanism for creating the scientific and innovation component of the cluster as a fully-fledged newly created cluster element are investigated. We show that the cluster should be created on the basis and strict adherence to fundamental organizational and economic principles. In particular, while in holdings the economic result of the activity is aimed at achieving the goals of the parent company, in a cluster the maximum interest in the result and the satisfaction of the economic interests of all participants in equal measure should be laid. Moreover, the classical cluster approach in the current market conditions may be unrealizable and the author's concept of cluster development is preferable.
Keywords: O13; Q19; R12; 330; cluster; rural economy; mechanism